2010
DOI: 10.1016/j.febslet.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Structural implications for K5/K12‐di‐acetylated histone H4 recognition by the second bromodomain of BRD2

Abstract: The BET family proteins recognize acetylated chromatin through their two bromodomains, acting as transcriptional activators or tethering viral genomes to the mitotic chromosomes of their host. The structural mechanism for how the N-terminal bromodomain of human BRD2 (BRD2-BD1) deciphers the mono-acetylated status of histone H4 tail was recently reported. Here we show the crystal structure of the second bromodomain of BRD2 (BRD2-BD2) in complex with the di-acetylated histone H4 tail (H4K5ac/K12ac). To our surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…While single bromodomains from Brd2 have been shown to attach to histone peptides in vitro (Huang et al, 2007;Nakamura et al, 2007;Umehara et al, 2010a;Umehara et al, 2010b), we have observed chromosome dissociation of a construct encompassing both intact bromodomains in the cell, highlighting the relevance of other structural characteristics in the context of the full-length protein for chromatin association in vivo. In this regard, motif B seems to be specifically required for chromosome association, since deletions of similar extent, N-terminal or Cterminal to motif B, do not affect Brd2 behavior or function.…”
Section: Role Of Motif B In Chromatin Recognitionmentioning
confidence: 73%
See 2 more Smart Citations
“…While single bromodomains from Brd2 have been shown to attach to histone peptides in vitro (Huang et al, 2007;Nakamura et al, 2007;Umehara et al, 2010a;Umehara et al, 2010b), we have observed chromosome dissociation of a construct encompassing both intact bromodomains in the cell, highlighting the relevance of other structural characteristics in the context of the full-length protein for chromatin association in vivo. In this regard, motif B seems to be specifically required for chromosome association, since deletions of similar extent, N-terminal or Cterminal to motif B, do not affect Brd2 behavior or function.…”
Section: Role Of Motif B In Chromatin Recognitionmentioning
confidence: 73%
“…However, additional acetylation marks have been reported to be recognized by Brd2, for instance acetyl-K5 and acetyl-K8 on histone H4 (Kanno et al, 2004;Umehara et al, 2010b). It is worth noting that these marks decrease during mitosis (Kruhlak et al, 2001;Sasaki et al, 2009).…”
Section: Role Of Motif B In Chromatin Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…BET proteins bind to acetylated histone tails via their bromodomains (44,45). The structures of BRD2 bromodomains BD1 and BD2 have been solved in association with H4 acetylated on Lys-5 and -12 (46,47). Recently, small-molecule inhibitors of BET proteins (I-BET and JQ1) have been developed that disrupt the binding interface between the bromodomain and the acetylated lysine groups on chromatin (48)(49)(50)(51).…”
mentioning
confidence: 99%
“…119 The complexity of BRDcontaining proteins role in the regulation of gene expression can be exemplified by the BRDs in human SWI/SNF BRG1 and hBRM ATPases, which have dynamic capacity to bind H3K14ac, H4K8ac, H4K5ac and H4K122ac, as well as DNA, via AT-hook or zinc finger binding motifs. [122][123][124][125] This is also exemplified by the Brg-1 component of remodeling complex BAF, which contains two bromodomains (BD 1 and BD 2 ) with capacity to trigger transcription through association with transcription factor E2F, transcription mediators such as CDK8 and TRAP220, RNAP II, 119 and with ability to dock to acetylated histone tails. 126 Other human BRD proteins, such as Brd4, are also recruited to acetylated H3/H4 tails or phosphorylated H3S10 and, in turn, recruit enzymes that phosphorylate RNAP II and recruit P-TEFb to transcriptional start sites.…”
Section: Heterochromatin Proteinsmentioning
confidence: 99%